Training Leadership and Critical Mind Through SWOT Analysis in 8th Grade Students at Ma’arif Middle School, Batu City - Nuraziza , Chandra Putri; Nugroho, Muhammad Ilham; Azelia, Ranum Dyah Titah; Syahrani, Rizky Aura; Putri, Salsabilla Meidiana; Novitasari, Zahra Rizki (Tarqabin Nusantara Group, 2023)
A truly moral human means a quality human being who is involved in life, whether as a citizen, leader or being led. Because to become a complete human being, you must know yourself. In order to create a national generation that is superior and competitive and has the spirit of a good leader, the Community Health Science Service team has taken steps to carry out community service in the form of outreach regarding